Over 89% of Patients Return to Work After Undergoing Arthroscopic or Open Latarjet Procedure for Anterior Shoulder Instability: A Systematic Review - Lee, Michael S; Patel, Seema M; Klug, Trevan; Moran, Jay; Park, Nancy; Mahatme, Ronak J; Fong, Scott; Gillinov, Stephen M; Dawes, Alexander; Surucu, Serkan; Graf, Alexander; Jimenez, Andrew E (Arthroscopy, 2025)
To better define the rate of return to work in patients undergoing Latarjet surgery for anterior shoulder instability. A systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. PubMed, Cochrane Center Register of Controlled Trials, and Scopus were queried in October 2023 with the following keywords: ((latarjet) OR (anterior shoulder instability)) AND ((work) or (compensation)). Articles were included if they reported return to work in patients (including military members) undergoing Latarjet surgery for traumatic anterior shoulder instability with bone loss and were written in English. This study was registered in Prospero (ID blinded). Six studies reporting on 419 shoulders were included in the review. Five studies reported on patients in the general population, and 1 reported on military members. Mean age ± standard deviation of patients ranged from 23.1 ± 5.8 to 32.0 ± 12.3 years. Moreover, there were 286 primary Latarjet procedures, 131 revision Latarjet procedures, and 2 unspecified as primary or revision surgery. Mean glenoid bone loss ranged from 14.5% to 22.9%. Return-to-work rates ranged from 89.1% to 100%, with 2 studies reporting all patients were able to return to work. Among military members, 89.1% were able to return to duty. Mean time to return to work ranged from 8.69 to 34.8 weeks after surgery. Four studies also reported return to sport, which ranged from 60.9% to 100%. Mean time for returning to sport varied between 10.0 and 35.2 weeks after the Latarjet procedure. Patients with anterior shoulder instability who undergo an arthroscopic or open Latarjet procedure can expect high rates of return to work and sport. All studies reported return-to-work rates over 89%, with 89.1% of military members able to return to duty. Level IV, systematic review of Level III and Level IV studies.